Financial Stability, Systems and Regulation - Kregel, Jan; Rezende, Felipe C.; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
Ever since the 2007–8 global financial crisis and its aftermath, Hyman Minsky’s theory has never been more relevant. Throughout his career, Jan Kregel has called attention to Minsky’s contributions to understanding the evolution of financial systems, the development of financial fragility and instability, and designing the financial structure necessary to support the capital development of the economy. Building on Minsky, Kregel developed a framework to analyze how different financial structures develop financial fragility over time. Rather than characterizing financial systems as market-based or bank-based, Kregel argued that it is necessary to distinguish between the risks that are carried on the balance sheets of banks and other financial institutions. This volume, brought together by Felipe C. Rezende, highlights these major contributions from Kregel through a collection of his influential papers from various journals and conferences. Kregel’s approach provides a strong theoretical background to understand the making and unfolding of the crisis and helps us to draw policy implications to improve financial stability, and suggest an alternative financial structure for a market economy. In this book, his knowledge is consolidated and the ideas he puts forward offer a path for future developments in economics which will be of great interest to those studying and researching in the fields of economics and finance.
Preface, --Acknowledgments. --I. The Evolution of Financial Systems.-- --1.The Past and Future of Banks. 2.Financial Fragility and the Structure of Financial Markets. 3.Universal Banking, US Banking Reform and Financial Competition in the EEC. 4. Market Forms and Financial Performance. 5. Some Considerations on the Causes of Structural Change In Financial Markets. --II. Minsky-Fisher, Financial Instability. --6. Margins of Safety and Weight of the Argument in Generating Financial Fragility. 7. Managing the Impact of Volatility in International Capital Markets in an Uncertain World . 8. The Natural Instability of Financial Markets. --III. Minskys Theory in an International Context: Financial Globalization and Emerging Markets.--9.Currency Stabilization through Full Employment: Can EMU Combine Price Stability with Employment and Income Growth?.10. Yes, It Did Happen Againa Minsky Crisis Happened in Asia. 11. The Brazilian Crisis: From Inertial Inflation to Fiscal Fragility.12. Financial Liberalization and Domestic Policy Space: Theory and Practice with Reference to Latin America.13. Emerging Markets and the International Financial Architecture: A Blueprint for Reform. --IV. Financial Stability as a Chimera.--14. Using Minsky to Simplify Financial Regulation.15.Minsky and Dynamic Macroprudential Regulation. Index
Includes bibliographical references and index.
Also available in print format.
Keywords: BUSINESS & ECONOMICS / Banks & Banking; economic policy; financial crisis; financial instability; financial institutions; financial systems; hyman minsky; jan kregel; Financial crises; Financial crises -- Prevention; Business cycles; Economic development; Financial institutions -- Law and legislation; elektronické knihy; electronic books